Unleashing innovation: 3D-printed biomaterials in bone tissue engineering for repairing femur and tibial defects in animal models – a systematic review and meta-analysis - Sagar, Nitin; Chakravarti, Bandana; Maurya, Shailendra S.; Nigam, Anshul; Malakar, Pushkar; Kashyap, Rajesh (Frontiers in Bioengineering and Biotechnology, 2024)
3D-printed scaffolds have emerged as an alternative for addressing the current limitations encountered in bone reconstruction. This study aimed to systematically review the feasibility of using 3D bio-printed scaffolds as a material for bone grafting in animal models, focusing on femoral and tibial defects. The primary objective of this study was to evaluate the efficacy, safety, and overall impact of these scaffolds on bone regeneration. Electronic databases were searched using specific search terms from January 2013 to October 2023, and 37 relevant studies were finally included and reviewed. We documented the type of scaffold generated using the 3D printed techniques, detailing its characterization and rheological properties including porosity, compressive strength, shrinkage, elastic modulus, and other relevant factors. Before incorporating them into the meta-analysis, an additional inclusion criterion was applied where the regenerated bone area (BA), bone volume (BV), bone volume per total volume (BV/TV), trabecular thickness (Tb. Th.), trabecular number (Tb. N.), and trabecular separation (Tb. S.) were collected and analyzed statistically. 3D bio-printed ceramic-based composite scaffolds exhibited the highest capacity for bone tissue regeneration (BTR) regarding BV/TV of femoral and tibial defects of animal models. The ideal structure of the printed scaffolds displayed optimal results with a total porosity >50% with a pore size ranging between 300-and 400 µM. Moreover, integrating additional features and engineered macrochannels within these scaffolds notably enhanced BTR capacity, especially observed at extended time points. In conclusion, 3D-printed composite scaffolds have shown promise as an alternative for addressing bone defects.